A Hadhrami Scholar and Islamic Court in Aceh: The Political Biography of ‘Abd al-Raḥmān al-Ẓāhir (1864-1878) - Mehmet Özay (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
‘Abd al-Raḥmān al-Ẓāhir (1833-1896) was an influential, dynamic Hadhrami. He was a Muslim reformer, as well as a savvy businessman and formidable diplomat. Arriving in Aceh in 1864, he embarked on both business and political endeavors, as religious and trade experiences helped develop diplomatic ties between the locals, the Ottomans, and the European powers. Although he surrendered in 1878 to the Dutch, his activities and influence were increasingly common subjects for different colonial newspapers until the middle of the 20th century. This article re-examines al-Ẓāhir’s political role and his various interactions with Acehnese royal contends. It investigates his interactions with the Aceh court, the uleebalang, and the Dutch, as well as the socio-political environment that informed his surrender to the Dutch. Through investigations of numerous Ottoman, Dutch and indigenous sources, this article offers a glimpse into the reality of the indigenous responses to the decisions of this most trusted Hadhrami.